Innovative methods of treating drug-resistant epilepsy: Review of the latest reports - Fatyga, Patrycja; Fatyga, Wiktoria; Kowalik, Piotr; Pabis, Gabriela; Wziątek, Joanna; Bętkowska, Paula; Koziołek, Iwona; Strzelczyk, Magdalena; Krzyżanowska, Daria; Dowierciał, Kinga (Quality in Sport, 2025)
Information and purpose: Drug-resistant epilepsy (DRE) affects about one-third of epilepsy patients, posing a serious challenge despite numerous available antiepileptic drugs. For patients who do not respond to pharmacological treatment, alternative approaches are needed. This study aims to present selected non-pharmacological methods for treating DRE. Material and methods: The review is based on publicly available sources, focusing on articles published between 2020 and 2025 in the PubMed database. Historical context was drawn from literature dating back to the 1990s. Results: Common non-pharmacological treatments include surgery, neurostimulation, and the ketogenic diet. These methods have proven effective in reducing seizure frequency and improving quality of life. They offer personalized and well-tolerated options suitable for different age groups. Conclusions: Non-pharmacological treatments for DRE are valuable alternatives for patients not benefiting from medication. Their efficacy and safety support their growing use in modern clinical practice.